Money endogeneity and interest rates (1994)
Based on the post-Keynesian theories of endogenous money, this worklays out the basis of a research program on the Colombian monetaryeconomy. The usual interpretation of the quantitative equation formoney considers that income and the velocity of circulation of moneyare constant, while the volume of money is controlled by theauthorities and changes in it are translated into changes in the levelof prices: the amount of money in circulation causes prices to be whatthey are, and is exogenous to them. A Post-Keynesian interpretationwould say that price increases bring a greater demand for money, andthat, in the name of the stability and solidity of the banking system,the central bank should adapt to such changes. Prices affect the moneysupply, and money is therefore endogenous. The article discusses thetheoretical problems of this approach and presents empirical evidencesupporting the hypothesis in the case of Colombia, suggesting analternative way of managing interest rates.